TEACHING READING COMPREHENSION USING TASK JOURNALS - Yusri - - (Politeknik Negeri Sriwijaya, 2009)
The ability to comprehend the reading text is very important. Reading is the dominant skill in learning any subjects, because the ability to read is not only the performance to pronounce the passage, but also the comprehension of the written message. Since reading is not an easy skill to master, the teaching of reading must be programmed in such a way in order to help the students understand the reading material well. By giving them the reading techniques such as skimming and scanning techniques, the students can be consequently reduce time spent in reading by one half time. This paper will look at the design, implementation, and integration of a task journal that is designed to : 1) stimulate students’ thinking about the texts, 2) promote reflection on the reading process, 3) give students practice with a practical strategy for vocabulary building, and 4) serve as a basis for assessment of students reading.